Temporal variability of the invasive Asian clam Corbicula fluminea (Müller, 1774) in the Poxim-Açu River, northeastern Brazil - Rosa, Leonardo Cruz da; Dantas, José Oliveira (Acta scientiarum. Biological sciences, 2025)
In this study we analyze the temporal variability in the density and the size classes of the Corbicula fluminea (Müller, 1774) at Poxim-Açu River, northeastern Brazil. Densities ranged from 60 ± 103 to 500 ± 240 individual m-², but this variability was not statistically significant. There was no significant relationship between densities and water parameters (depth and flow). The population was mainly composed of young individuals, with 10-14 mm of shell length. Lower densities and predominance of juveniles suggest a recent invasion event. However, C. fluminea was firstly recorded at Poxim-Açu River three years before this study. Thus, these results might reflect a mortality followed by a reinvasion event. A continuous monitoring program is needed to better evaluate whether this population is growing and spreading as well as to determine which environmental variables could be driving the temporal variability of this species.